Higher Education Geographic Expansion Strategic Model in Iran: A Qualitative Study - Shahram Yazdani; Maryam AkbariLakeh (Tabriz University of Medical Sciences, 2016)
Background: After the Islamic revolution in Iran, university admission multiplied greatly in a short time. In addition to considering the policy that guides the action plan to expand higher education (HE), we need to design strategic planning in this area for sustainable development.The main objective of this study was to create a model for how to develop HE in different geographic places in our country. Methods: According to the policy of HE development, we designed this study in the Ministry of Health and Medical Education (MOHME) to find out how to foster the development of HE in different geographic places in our country. For developing a HE geographic expansion model (HEGEM) appropriate to our country, Hugh McKenna's qualitative concept analysis was designed and performed over 2 years. First, the problems were detected, and then conceptually clarified and analyzed. After that, we compared our primary model components, which were obtained at the end of the analysis, with the experiences of different countries, and then revised our model. Then, in order for the extracted preliminary policy draft of HEGEM to be applicable in the country, an expert panels' group discussions and policy survey were implemented by 8 experts in policy making and HE program administrations. Lincoln and Guba eligibility criteria were considered. Results: Eight themes were extracted that greatly affected HEGEM in health systems and medical education in Iran including massification of HE, capacity for self-actualization in HE,types of division in HE, the appropriate number of HE institutions, size of HE centers, access to elite universities and avoidance of migration within the country, decentralization of HE and development of spatial planning for the public health network. The policy operational model of HEGEM was finalized and presented as a practical package for implementation in the whole country. Conclusion: For promotion of community health and improvement of the national and international position of Iran's medical universities and HE centers, policymakers should consider the diverse factors that influence HE expansion in our developed model.